“No one told me”: exploring factors influencing physical activity participation in Black Nova Scotian cancer survivors - Chiekwe, C. Joy; Hamilton-Hinch, Barbara; Grandy, Scott A.; Fowles, Jonathon; Keats, Melanie R. (Frontiers in Cancer Control and Society, 2024)
Background: Few studies have examined differences in cancer survivors’ physical activity and exercise behaviors by race/ethnicity and none have explored this relationship in a Canadian context. Purpose: To explore the underlying factors that influence physical activity and exercise participation in African, Caribbean, and Black (ACB) cancer survivors. Methods: Semi-structured interviews were conducted with eight ACB cancer survivors residing in Nova Scotia, Canada. Interviews broadly explored three main topics: 1) Exploring physical activity and exercise knowledge; 2) Barriers and facilitators to physical activity and exercise; and 3) Perceptions of cancer specific exercise trials and programs. Participant interviews were audio-recorded and transcribed verbatim and analyzed using an inductive thematic analysis. Results: An overall storyline of ‘No One Told Me’ along with four primary themes emerged from the participant interviews. Theme 1, ‘The Journey’ describes the lack of knowledge sharing between healthcare providers and cancer survivors. Theme 2, ‘What’s There For Me’ unravels participants understanding of physical activity and exercise, knowledge of available support, and guidance to maintain and/or improve well-being through exercise. Theme 3, ‘One Step at a Time’ spotlights participants thoughts and perceptions of participating in physical activity and exercise. Theme 4, ‘See ME’, considers recommendations to increase awareness and participating in physical activity and exercise trials/programs and the importance of providing safe and welcoming spaces for all. Discussion: This study offers insight into the barriers confronted by ACB cancer survivors when considering participation in physical activity and exercise. Participants were largely aware of the benefits of being physically active but described a lack of perceived knowledge sharing and welcoming spaces. Further investigation is needed to identify strategies to improve representation of ACB cancer survivors in clinical exercise studies and community, cancer-specific exercise programming.